1997
DOI: 10.1002/eji.1830270131
|View full text |Cite
|
Sign up to set email alerts
|

γδ cells involved in contact sensitivity preferentially rearrange the Vγ3 region and require interleukin‐7

Abstract: Ptak and Askenase showed that both alphabeta and gammadelta cells are required for transfer of contact sensitivity (CS). This study confirms that day 4 immune cells depleted of gammadelta cells fail to transfer CS to trinitrochlorobenzene (TNP-Cl) systemically and demonstrates that administration of anti-gammadelta monoclonal antibodies (mAb) in vivo abolishes the CS reaction. Moreover, gammadelta cells accumulate at the antigen challenge site: these cells have the unusual phenotype CD8alpha+, CD8beta-, IL-4 R… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
42
0

Year Published

1999
1999
2020
2020

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 31 publications
(43 citation statements)
references
References 39 publications
1
42
0
Order By: Relevance
“…As we found an increased number of IL-17A + and IFN-γ + DETC in the skin following exposure of the skin to DNFB, we wanted to investigate the effect of anti-CD3 and IL-1β on IFN-γ production by DETC. Furthermore, as the role of γδ T cells during CHS has been suggested to be anti-inflammatory we investigated if treatment with anti-CD3 and IL-1β lead to induction anti-inflammatory cytokines IL-10 and/or TGFβ(17,18,22,23). Treatment with anti-CD3 induced the production of both IFN-γ and IL-10 (Figure 3D).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…As we found an increased number of IL-17A + and IFN-γ + DETC in the skin following exposure of the skin to DNFB, we wanted to investigate the effect of anti-CD3 and IL-1β on IFN-γ production by DETC. Furthermore, as the role of γδ T cells during CHS has been suggested to be anti-inflammatory we investigated if treatment with anti-CD3 and IL-1β lead to induction anti-inflammatory cytokines IL-10 and/or TGFβ(17,18,22,23). Treatment with anti-CD3 induced the production of both IFN-γ and IL-10 (Figure 3D).…”
Section: Resultsmentioning
confidence: 99%
“…In adoptive transfer experiments, γδ T cells have been found to assist αβ T cells in mediating the CHS response in a non-allergen and non-MHC specific manner (21). The role of γδ T cell help in the CHS response was further investigated, and DETC were identified as the γδ T cell assisting the αβ T cells (17,18). Furthermore, in vitro studies found that keratinocytes could induce DETC proliferation in a non-MHC restricted way following exposure to various contact allergens, whereas exposure to irritants could not (20).…”
Section: Introductionmentioning
confidence: 99%
“…␥␦ T cells abrogate oral tolerance measured by Ig production (44). Other reports have shown that ␥␦ T cells were indispensable in successful transfer of contact hypersensitivity by T cells (45,46). In contrast, ␥␦ T cells may also participate actively in the suppression of the ␣␤ T cell response (47,48).…”
Section: Discussionmentioning
confidence: 97%
“…In contrast, IL-7 is a keratinocyte-derived growth factor important for the development of ␥␦T cells, including mouse dendritic epidermal T cells (DETC) (27). Expression of this cytokine is increased in psoriasis (28), and injection of an anti-IL-7 Ab inhibits ␥␦T cell accumulation in lymph nodes following skin sensitization (29,30). Moreover, transgenic mice overexpressing IL-7 in keratinocytes develop a lymphoproliferative skin disease (31)(32)(33)(34).…”
Section: Discussionmentioning
confidence: 99%